Contamination of ‘in-use’ bar soaps in dental clinics of University hospital - Sharma, Jyoti; Mehta, Manjula; Bhardwaj, Sonia Bhonchal (International Journal Of Community Medicine And Public Health, 2021)
Hand carriage of bacteria is an important route of transmission of infection in health care settings. Hand washing continues to be the most effective mechanism of prevention of the spread of infection in hospitals. In this study the ‘in-use’ bar soaps in the dental hospital were sampled to look for the presence of microorganisms on their surfaces. All the soaps which were sampled yielded the growth of microorganisms on them. The isolated microorganisms are Bacillus, Micrococci, Staphylococci and gram-negative bacilli. Since the use of ‘in-use’ bar soaps function as reservoir of microorganisms so contact free soap dispensers, soap strips or liquid soap should be used in hospital settings to prevent the transmission of microorganisms.